Kandungan Protein Pada Kecap Air Kelapa Dengan Penambahan Tepung Belalang Kayu Dan Sari Buah Nanas - Irtasari., Irtasari; , Dra. Aminah Asngad, M.Si (2015)
Waste of coconut water has a lot of nutrient to make ketchup. Protein content in coconut water is low. Thus, in the response of solving the problem,it might be beneficial if added materials that contained high protein, like grasshopper. Regarding the process of making the ketchup, byusing pineapple extract could accelerate the process of hydrolysis because pineapple actually contained the enzymebromelin. Therefore, this study was made to determine the protein content and the organoleptic inside the ketchup. While the method of the study used a Complete Randomized Design with two factors, named concentration of the additional pineapple extract (L), and the additional of grasshopperflour (S). The results showed that there were differences in the levels of protein inside ketchup coconut water with grasshopper flour and pineapple extract. The highest protein content on the treatment of grasshopper flour 10 grams with pineapple extract 75% is 3.502 and the lowest protein content on the treatment of grasshopper flour 5 grams and pineapple extract 75% is 1,509. Based on the research findings, the results of organoleptic tests howed different results for each treatment.